STRUCTURAL ERRORS IN LITERARY ANALYSIS WRITE-UPS AMONG SENIOR HIGH SCHOOL STUDENTS - Dichoso, David (International Journal of Arts, Sciences and Education, 2021)
Error Analysis (EA) of learners’ written output is a tool that can bridge the learning gaps and the teaching direction of every English teacher. EA enables teachers to identify and analyze sentence errors, and its results will lead the teacher to understand and address the causes of errors committed. This descriptive-qualitative study analyzed learners’ structural errors in their literary write-ups. Corder’s Stages in error analysis was employed in analyzing the errors committed by Senior High School student participants. The evidence of the structural errors indicated that at the sentential level, the prevalent errors are Disagreement of Verb and Subject, Incorrect Verb Tense, and Missing Punctuation. The most dominant errors committed for the word level are Incorrect Articles, Incorrect Spelling, and Incorrect Prepositions. From these findings, the errors committed by the learners are associated with their first language or mother tongue. Errors manifested are also caused by learners’ carelessness in writing, and limited knowledge in the rules of English grammar. Moreover, these results call for teachers to value such research findings, for it can be a basis to upscale teaching pedagogies, create and innovate contextualized learning materials, and recalibrate assessment and evaluation tools to improve the written grammatical competence of learners. Furthermore, teachers are also encouraged to conduct error analysis of their learners’ outputs, for the results will reflect the learning gaps in grammar that need to be addressed.